2019
DOI: 10.1080/15548627.2019.1596480
|View full text |Cite
|
Sign up to set email alerts
|

GORASP2/GRASP55 collaborates with the PtdIns3K UVRAG complex to facilitate autophagosome-lysosome fusion

Abstract: It has been indicated that the Golgi apparatus contributes to autophagy, but how it is involved in autophagosome formation and maturation is not well understood. Here we show that amino acid starvation causes trans-Golgi derived membrane fragments to colocalize with autophagosomes. Depletion of the Golgi stacking protein GORASP2/GRASP55, but not GORASP1/GRASP65, increases both MAP1LC3 (LC3)-II and SQSTM1/p62 levels. We demonstrate that GORASP2 facilitates autophagosome-lysosome fusion by physically linking aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 55 publications
3
54
3
Order By: Relevance
“…, 2016 ) and that there is a link between Golgi function and autophagy ( Zhang et al. , 2018 , 2019 ). However, this possibility was ruled out by BafA1 treatment, which inhibits lysosomal degradation but not Arl1 and Golgin-97 degradation in H 2 O 2 -treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…, 2016 ) and that there is a link between Golgi function and autophagy ( Zhang et al. , 2018 , 2019 ). However, this possibility was ruled out by BafA1 treatment, which inhibits lysosomal degradation but not Arl1 and Golgin-97 degradation in H 2 O 2 -treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Enhance autophagy induction and promote autophagosome-lysosome fusion Phospholipid binding C2 domain √ √ (Liang et al, 2008;He et al, 2013;Zhang et al, 2019) WIPI2 WIPI4 Atg18 Atg21 PI3P binding protein: WIPI2 recruits ATG12∼ATG5-ATG16L1 to phagophore, retrieves of ATG9 from early autophagosome membranes; WIPI4 can bind with ATG2 in the regulation of lipid transfer 6CD loop in ß-propeller structure √ √ (Watanabe et al, 2012) Lipids and membrane-associated proteins in autophagy Ichimura et al, 2000;Nath et al, 2014) ATG5…”
Section: Vps38mentioning
confidence: 99%
“…colleagues demonstrated that cysteine-mediated oligomerization of ATG14 promotes the fusion of autophagosomes and lysosomes by tethering these two organelles and it can assist STX17 to recruit SNAP29 to autophagosomes promoting the assembly of SNARE complex (Diao et al, 2015). Besides, from the genetic analysis, the HOPS complex also plays a crucial role in the fusion between autophagosomes and lysosomes, likely through tethering of these two organelles together with SNAREs, Rabs, and other tethering related proteins such as PLEKHM1 (Pleckstrin homology domain-containing family M member 1) (McEwan et al, 2015), UVRAG (UV radiation resistance-associated protein) (Liang et al, 2008), EPG5 (Ectopic P granules protein 5 homolog) (Wang et al, 2016), BRUCE (BIR repeat-containing ubiquitin-conjugating enzyme) (Ebner et al, 2018), TECPR1 (Chen et al, 2012), GRASP55 (Golgi reassemblystacking protein 55) (Zhang et al, 2019), and etc. Together, these proteins might behave as a template for SNAREs to register and assemble on it, or to expand the fusion pore as we learned from the biochemical studies of yeast vacuole fusion (Liang et al, 2008;Jiang et al, 2014;McEwan et al, 2015;Ding et al, 2019).…”
Section: Autophagosome-lysosome Fusionmentioning
confidence: 99%
“…Upon glucose starvation, GORASP2 is de-O-GlcNAcylated and acts as a membrane tether to facilitate autophagosome-lysosome fusion (Zhang et al, 2018). Additionally, GORASP55 interacts with BECN1 to facilitate the assembly and membrane association of the PtdIns3K UVRAG complex (Zhang et al, 2019). Furthermore, GRASP55 displays positive regulatory effects on autophagy induction and influences the lipidation of LC3b (Dupont et al, 2011).…”
Section: Gorasp2/grasp55mentioning
confidence: 99%